Strategi Pemasaran Syariah Produk Tabungan Ukhuwah pada BPRS Daya Artha Mentari bagi Pelaku UMKM Halal - Cendi Fibtia; Aslikhah; Sukamto (Kartika: Jurnal Studi Keislaman, 2026)
The development of the Islamic banking sector in the country forces financial institutions to adopt marketing tactics that are efficient and in line with Sharia principles. PT. BPRS Daya Artha Mentari introduced the Ukhuwah Savings product with a profit-sharing mechanism and a lottery program to attract public attention, especially for MSMEs that operate according to Sharia. Nevertheless, there are still obstacles such as low understanding of Islamic finance and public perception of the product. This study aims to evaluate the Islamic marketing approach as well as the Ukhuwah Savings services and ways to attract the interest of halal MSME actors in Pasuruan Regency. The method used is qualitative with a descriptive approach. Data were collected through observation, interviews, and documentation from informants from the marketing department and MSME customers based on Sharia. Research findings indicate that the implemented sharia marketing strategy already reflects the values of shiddiq, amanah, tabligh, and fathanah. The marketing process is carried out directly, through brochure distribution, as well as utilizing digital platforms such as WhatsApp and Instagram. The services provided are friendly, responsive, and adaptive through a pick-up system. This strategy is stated to be effective in increasing the interest of halal MSME actors in Tabungan Ukhuwah, although improvements are still needed in education, information transparency, and promotion strengthening to build trust and customer numbers sustainably.